Peculiar Presentation of Ulcerative Colitis - Hamdy M. A. Ahmed; Amany Diab; Ayman Ahmed; Samar Abohamad; Hala Elgendy (Case Reports in Gastrointestinal Medicine)
Ulcerative colitis (UC) is a chronic inflammatory and recurrent disorder that is characterized by bowel inflammation. Among the extraintestinal manifestations (EIMs) that associate UC are the joints and renal manifestations. Joint affection in the form of arthritis can precede the intestinal manifestations of UC. However, renal affection with amyloidosis does not precede the UC diagnosis. Herein, we report a case of 26-year-old male diagnosed with UC after having peripheral arthritis for long time in addition to spondylitis and kidney amyloidosis.